S27 Cardiovascular events following Clarithromycin use in lower respiratory tract infections: analysis of two prospective cohort studies. (19th November 2012) - Singanayagam, A; Short, P; Williamson, P; Akram, A; Fleming, G; Taylor, J; Higgins, S; Mills, D; Singanayagam, A; Archibald, R; Peet, L; Hill, AT; et al.
Abstract : Background: Previous studies have suggested that use of macrolide antibiotics may increase cardiovascular risk. Objective: To study the effects of clarithromycin on cardiovascular events in the setting of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) and community acquired pneumonia (CAP). Design: Cohort study of two prospectively collected datasets; a multicentre observational study of patients hospitalised with AECOPD and the Edinburgh pneumonia study cohort. Setting: COPD dataset includes patients admitted to one of 12 hospitals around the United Kingdom between 2009–2011. The Edinburgh pneumonia study cohort includes patients admitted to NHS Lothian Hospitals between 2005–2009. Main outcome measures: Hazard ratios (HR) for cardiovascular events at 1 year (defined as hospitalised with acute coronary syndrome (ACS), decompensated cardiac failure, serious arrhythmia or sudden cardiac death) and hospitalisation for acute coronary syndrome (acute ST elevation myocardial infarction, non-ST elevation MI and unstable angina). Secondary outcomes were all cause and cardiovascular mortality at 1 year. Cox proportional hazard regression was used to calculate hazard ratio's and 95% confidence intervals after adjusting for significant covariates. Results: There were 1323 and 1631 patients in the AECOPD and CAP cohorts with 268 and 171 cardiovascular events respectively over 1 year. Macrolide use in AECOPD was associated with increased risk of cardiovascular events HR 1.60 (1.17–2.20) and ACS HR 1.88 (1.16–3.01). Macrolide use in CAP was associated with increased risk of cardiovascular events HR 1.81 (1.28–2.55) and ACS HR 1.90 (1.07–3.33). There was a significant association between macrolide use and cardiovascular but not all cause mortality in AECOPD HR 1.67 (1.11–2.51) and 1.24 (0.96–1.61). Macrolide use in CAP was associated with a trend towards increased risk of all cause and cardiovascular mortality HR 1.13 (0.85–1.51) and 1.57 (0.84–2.82). These relationships persisted after propensity matching. Statins and other cardiac drugs attenuated this increased risk. Longer durations of macrolide use were associated with more cardiovascular events. The effect of macrolides was most evident in patients with pre-existing cardiovascular disease or at high risk of cardiovascular disease according to the QRISK2 score. Conclusions: The use of clarithromycin in the setting of AECOPD or CAP is associated with increased cardiovascular events.